Real-World Outcomes of Endovascular Management of Intracranial Aneurysms: Insights from a Tertiary Care Hospital in Central India - Yadav, Nishtha; Hedaoo, Ketan; Patidar, Jayant; Parihar, Vijay Singh; Ratre, Shailendra; Tamaskar, Aparna; Jain, Anivesh; Ravi, Saranya; Mahajan, Vinayak; Singh, Amar Pratap (Journal of Clinical Interventional Radiology ISVIR, 2025)
Endovascular coiling has emerged as a preferred treatment for intracranial aneurysms (IAs), offering better functional outcomes than surgical clipping. This study examines the demographic and clinical profiles of patients with IAs, evaluates the success of various endovascular techniques, and reports associated complications in a publicly funded tertiary care hospital in Central India.This retrospective study included 100 patients (103 aneurysms) treated from March 2021 to December 2023. Data on aneurysm morphology, rupture status, and treatment modality were analyzed. Procedures included simple coiling, balloon-assisted coiling, stent-assisted coiling, flow diverters, and braided stent monotherapy. Outcomes were assessed using the modified Rankin Scale (mRS) and angiographic Modified Raymond–Roy Classification. Complications like vasospasm and thromboembolic events were recorded, and linear regression was used to identify factors influencing outcomes.Aneurysms were mostly saccular (91%) and located in the anterior circulation (83.5%). Favorable outcomes (mRS 0–2) were achieved in 81.5% of patients at discharge, with 91.7% maintaining functional independence during follow-up (3 months to 2 years).Complications included thromboembolic events (6.5%), intraoperative rupture (1.9%), and coil migration (1%). Complete aneurysm occlusion was achieved in 74.4% of cases available for angiographic follow-up. Poor outcomes were associated with high World Federation of Neurosurgical Societies grade, vasospasm, and thromboembolic events. Mortality was 14.1%.Endovascular coiling is effective in achieving functional independence and aneurysm occlusion, comparable to global standards. However, complications like vasospasm and thromboembolic events emphasize the need for individualized care and long-term follow-up in resource-limited settings.
Keywords: coiling; aneurysm; endovascular